Limiting deoxynucleoside triphosphate concentrations emphasize the processivity defect of lamivudine-resistant variants of human immunodeficiency virus type 1 reverse transcriptase. - Back, N K (1997)
The nucleoside drug lamivudine (3TC) triggers the selection of resistant forms of the human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) with a substitution of amino acid 184Met. The 3TC-resistant RT enzymes 184Val and 184Ile exhibit a processivity defect in in vitro assays that correlates with reduced replication of the corresponding virus variants in primary cells. However, no replication defect is apparent for these two mutants in the transformed T-cell line SupT1. One obvious difference between the two cell types is the intracellular deoxynucleoside triphosphate (dNTP) level. Primary cells have a much smaller dNTP pool, and this cellular condition may emphasize the processivity defect of the codon 184 RT variants. Alternatively, cell-specific cofactors that influence the process of reverse transcription may exist. Such accessory factors may be packaged into the virion to exert an effect on the RT enzyme. To discriminate between these possibilities we performed additional assays with the wild-type and mutant RT enzymes. The RT proteins were either isolated from virions produced by primary and transformed cell types or expressed as recombinant protein. We also performed infection assays with cells treated with a drug that reduces the intracellular dNTP pool. Furthermore, reverse transcription was studied within virus particles in the endogenous assay, which allows for the manipulation of the dNTP level. The combined results indicate that the enzymatic defect of the 3TC-resistant HIV-1 variants is stressed at low dNTP concentrations.